Decline of Enrolment in Quebec's English-language School Sector - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
The Charter of the French language (1977),1 also known as Bill 101, has had a strong and lasting impact on the English-language public school sector.2 Under this law, kindergarten to secondary school students whose Canadian parents or siblings were educated in Canada in English are entitled to English-language public education. Aside from a few exceptions, all other students must attend French-language schools. These educational clauses limit access to English-language schools3 by routing the children of newly arrived immigrants to French-language public schools,4 as well as restricting the access of Francophone Quebecers with no family history of attending English-language schools.
Parallel title: Education Research Brief no. 1
Keywords: Official Language Minority Community (OLMC)

Baisse des effectifs dans le secteur scolaire anglophone du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
La Charte de la langue française (1977)1, également connue sous le nom de Loi 101, a eu un impact fort et durable sur les écoles publiques de langue anglaise2. En vertu de cette loi, les élèves de la maternelle au secondaire dont les parents ou les frères et sœurs canadiens ont été instruits au Canada en anglais ont droit à une éducation publique en anglais. À quelques exceptions près, tous les autres élèves doivent fréquenter des écoles de langue française. Ces clauses éducatives limitent l’accès aux écoles de langue anglaise3 en orientant les enfants d’immigrants nouvellement arrivés vers les écoles publiques de langue française4, ainsi que l’accès des Québécois francophones qui n’ont pas des membres de leurs familles qui ont fréquenté des écoles de langue anglaise.
Parallel title: Résumé de recherche en éducation no 1
Keywords: Official Language Minority Community (OLMC)

Challenges Around Resources and Services in Quebec's English-language Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
English-language schools in Quebec struggle with diverse challenges, from urban and rural poverty to being located in isolated and remote areas. These issues impact the services and resources available to students and schools already constrained by a declining student population (Advisory Board on English Education [ABEE], 2018).
Parallel title: Education Research Brief no. 3
Keywords: Official Language Minority Community (OLMC)

Les enjeux en matière de ressources et de services dans les écoles de langue anglaise du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Ces enjeux ont un impact sur les services et les ressources disponibles pour les élèves et les écoles, déjà fragilisés par un effectif scolaire en constante diminution (Commission de l’éducation en langue anglaise [CELA], 2018).
Parallel title: Résumé de recherche en éducation no 3
Keywords: Official Language Minority Community (OLMC)

Provision of Services to Special Needs Students in Quebec's English-language Public Schools - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
In Quebec, a growing number of students are identified as having special needs, and it is currently estimated that this population represents one in five students (20.4%) in the public school system (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Parallel title: Education Research Brief no. 4
Keywords: Official Language Minority Community (OLMC)

Prestation de services aux élèves ayant des besoins particuliers dans les écoles publiques anglophones du Québec - Ciamarra, Nadine; Lamarre, Patricia; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2021)
Au Québec, un nombre croissant d’élèves sont identifiés comme ayant des besoins particuliers et on estime actuellement que cette population représente un élève sur cinq (20,4 %) dans le système scolaire public (Commission des droits de la personne et des droits de la jeunesse [CDPDJ], 2018).
Parallel title: Résumé de recherche en éducation no 4
Keywords: Official Language Minority Community (OLMC)